Orientalisme Vs Oksidentalisme: Benturan dan Dialogisme Budaya Global - Rohanda Rohanda; Dian Nurrachman (Jurnal Lektur Keagamaan, 2017)
Imperialism and colonialism have spawned research centers that examine the parts of the world that they control. Through these centers, orientalists work to discuss, write, produce and perform the Eastern world on the stage of Western culture. Authenticity, exoticism and grandeur of the East are dismantled, stripped down, doubted and elusive. Through orientalist goggles, the East is produced as a "hybrid" form; no more pure and original East. East is used as a storage or projection of their own unfamiliar (read: the West) aspects, such as crime, moral decadence, and so on. On the other hand, the East is seen as a dazzling world of exotic and full of mystical seductions. Meanwhile, unlike the orientalism that was originally intended as a serious study of the cultures to legitimize Western colonial powers in the Eastern world, occidentalism is precisely born from the methodological problems of orientalism which is said to be objective. Whereas behind the objectivity is stored Western interests to dominate, rearrange, and control the East. Orientalism has sparked nativist intellectuals to question the validity of orientalist works in constructing Eastern stereotypes. It cannot be denied then that these two discourses - Orientalism and Occidentalism - are in a position between the clashes and the global cultural dialogue.Keywords: Orientalism, oxidentalism, imperialism, colonialism, conflict, dialogue Imperialisme dan kolonialisme telah melahirkan pusat-pusat studi dan kajian yang menelaah belahan dunia yang dikuasainya. Melalui pusat-pusat kajian inilah, para orientalis bekerja untuk memperbincangkan, menulis, memproduksi dan mempertunjukkan dunia Timur di atas panggung kebudayaan Barat. Keaslian, keeksotisan dan keagungan Timur dibongkar, dipreteli, diragukan dan dibuat samar-samar. Melalui kacamata orientalis, Timur diproduksi sebagai suatu bentuk “hibrida”; tidak ada lagi Timur yang murni dan orisinal. Timur dijadikan tempat penyimpanan atau proyeksi dari aspek-aspek mereka sendiri (baca: Barat) yang tidak diakuinya, seperti kejahatan, dekadensi moral, dan lain-lain. Pada sisi lain, Timur dipandang sebagai dunia mempesonakan dari yang eksotis dan penuh dengan rayuan-rayuan mistis. Sementara itu, berbeda halnya dengan orientalisme yang sejak semula dimaksudkan sebagai kajian serius politik-budaya untuk melegitimasi kekuatan-kekuatan kolonial Barat di dunia Timur, oksidentalisme justeru lahir dari problem metodologis orientalisme yang katanya obyektif. Padahal di balik keobyektifan itu tersimpan kepentingan-kepentingan Barat untuk  mendominasi, menata kembali, dan menguasai Timur. Orientalisme telah memicu para intelektual nativis untuk mempertanyakan keabsahan (validitas) karya-karya para orientalis dalam membangun stereotip-stereotip ketimuran. Maka tidak dapat dipungkiri kemudian bahwa dua wacana ini — orientalisme dan oksidentalisme — berada dalam posisi di antara benturan dan dialogisme budaya global.Kata-kata kunci: orientalisme, oksidentalisme, imperialisme, kolonialisme, benturan, dialog